2021
DOI: 10.1051/e3sconf/202130601007
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses and yield of cauliflower (Brassica oleracea var. botrytis L.) to the delayed transplanting and drought stress

Abstract: Environmental condition is the main constrain of plant cultivation in riparian wetland. Transplanting time is frequently delayed due to flooding and the cultivated plants often experience drought stress during their generative stage due to insufficient water availability. The objective of this study was to evaluate the effect of delayed transplanting and drought stress on the growth and yield of cauliflower (Brassica oleracea Var. botrytis L.). The study was arranged based on the Factorial Randomized Block Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
1
0
1
Order By: Relevance
“…Perbedaan umur pindah tanam berpengaruh pada tinggi tanaman, jumlah daun per tanaman, luas daun per tanaman, diameter krop, berat prop, dan hasil krop (Pradhan and Singh, 2022). Penundaan pindah tanam selain berdampak negatif terhadap pertumbuhan dan hasil juga menyebabkan tertundanya umur panen (Kartika, et al, 2021). Umur pindah tanam dengan pemberian pupuk organik kotoran sapi pada tanaman sawi di lahan kering masih perlu dikaji guna mendapatkan informasi tentang kelayakan pemanfaatan kotoran sapi serta umur pindah tanam yang tepat khususnya untuk tanaman sawi di lahan kering.…”
Section: Pendahuluanunclassified
“…Perbedaan umur pindah tanam berpengaruh pada tinggi tanaman, jumlah daun per tanaman, luas daun per tanaman, diameter krop, berat prop, dan hasil krop (Pradhan and Singh, 2022). Penundaan pindah tanam selain berdampak negatif terhadap pertumbuhan dan hasil juga menyebabkan tertundanya umur panen (Kartika, et al, 2021). Umur pindah tanam dengan pemberian pupuk organik kotoran sapi pada tanaman sawi di lahan kering masih perlu dikaji guna mendapatkan informasi tentang kelayakan pemanfaatan kotoran sapi serta umur pindah tanam yang tepat khususnya untuk tanaman sawi di lahan kering.…”
Section: Pendahuluanunclassified
“…Furthermore, Kartika et al [26] reported the detrimental effects of delayed transplanting time on yield and plant growth indicators, such as leaf number, canopy area, and curd characteristics. Moreover, Sultana et al [27] found that the optimal transplanting time to maximize growth and yield also depends on cultivar and latitude.…”
Section: Yield and Growth Parametersmentioning
confidence: 99%